2022
DOI: 10.1038/s43586-022-00131-9
|View full text |Cite|
|
Sign up to set email alerts
|

Volume electron microscopy

Abstract: Life exists in three dimensions, but until the turn of the century most electron microscopy methods provided only 2D image data. Recently, electron microscopy techniques capable of delving deep into the structure of cells and tissues have emerged, collectively called volume electron microscopy (vEM). Developments in vEM have been dubbed a quiet revolution as the field evolved from established transmission and scanning electron microscopy techniques, so early publications largely focused on the bioscience appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 298 publications
(383 reference statements)
0
82
0
2
Order By: Relevance
“…These limitations can be overcome to some extent by volume Electron Microscopy (vEM). Volume EM includes all EM methods able to generate a continuous series of bidimensional projections from resin-embedded samples with a depth greater than 1 µm (Peddie et al, 2022). Among vEM techniques TEM based approaches are included, such as serial section TEM (ssTEM) and serial section Electron Tomography (ssET), as well as techniques based on the use of the Scanning Electron Microscope (SEM) to visualize the face of the embedded tissue block by means of the backscattered electrons.…”
Section: Volume Electron Microscopy Techniques In the Study Of Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations can be overcome to some extent by volume Electron Microscopy (vEM). Volume EM includes all EM methods able to generate a continuous series of bidimensional projections from resin-embedded samples with a depth greater than 1 µm (Peddie et al, 2022). Among vEM techniques TEM based approaches are included, such as serial section TEM (ssTEM) and serial section Electron Tomography (ssET), as well as techniques based on the use of the Scanning Electron Microscope (SEM) to visualize the face of the embedded tissue block by means of the backscattered electrons.…”
Section: Volume Electron Microscopy Techniques In the Study Of Synapsesmentioning
confidence: 99%
“…These methods allow the experimenters, by analyzing three-dimensional vEM datasets, to obtain information on tissues and cells ultrastructure on the x, y, and z axes. These different techniques, although having different spatial resolution (indeed they generate near TEM-quality ultrastructural data but still they do not reach TEM spatial resolution in the x, y axes) produce datasets from large volumes of tissue allowing for the segmentation and reconstruction of the structure under investigation (Titze and Genoud, 2016;Kubota et al, 2018;Peddie et al, 2022). Even if we recently reported that some relevant aspects of the postsynapse architecture can be faithfully evaluated from TEM bidimensional projections (Colombo et al, 2021), measures from reconstructed SEM-based vEM stacks proved to be the favorite choice when dealing with the analysis of postsynaptic organization and its structural plasticity.…”
Section: Volume Electron Microscopy Techniques In the Study Of Synapsesmentioning
confidence: 99%
“…Electron microscopy (EM) has played an essential role in understanding cell biology by revealing the intracellular organization in a vast variety of cells, tissues and small organisms (Introduction to Electron Microscopy of Cells, 2007). More recently, vEM methods have given the possibility to visualize ultrastructure in 3D (Peddie et al, 2022), opening the way to new discoveries. However, to date, these methods have been rarely applied to study marine microplankton.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest limitation of this technique, when imaging 3D cell cultures, is the lack of volumetric information which is essential to thoroughly appreciate cellular organisation in space. Conversely, volume electron microscopy (Peddie et al, 2022) and in particular focused ion beam-scanning electron microscopy (FIB-SEM) is an ideal solution to this problem. This method involves progressive specimen slicing by FIB surface ablation, followed by SEM imaging (Giannuzzi and Stevie, 2005; Heymann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these imaging methods alone can provide a complete structural and functional understanding across spatial scales of cells in the context of the complex multicellular environment of a 3D organoid. To alleviate such shortcomings, correlative approaches that combine the power of light and electron-based imaging modalities have been developed (Ganeva and Kukulski, 2020; Kukulski et al, 2011; Peddie et al, 2022). Yet, their implementation in organoid research has remained limited due to the diverse requirements these imaging modes have, which are rarely met by one single specimen preparation; established electron microscopy (EM) specimen preparation requires sample crosslinking by chemical fixation at room temperature, leading to disruption of the cells’ fine ultrastructure (Mollenhauer, 1991).…”
Section: Introductionmentioning
confidence: 99%